The Role of Social Media in the Formation of Religious Character in Children - Khairil Candra Wijaya; Rindang Ilma lestari; Nurul Imam; Muhammad Rizky Pratama (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2025)
Nowadays, teachers and books are no longer the only sources of knowledge available to students. Many other sources of knowledge can be accessed from the surrounding environment, social media has become an integral part of everyday life, the positive impact of social media provides wide access and easy access to educational and inspirational religious content such as lectures, articles, religion, and stories of the lives of pious people and become a platform for spreading positive messages and moral values ​​that are in accordance with religious teachings, while the negative impact is that children are vulnerable exposed to content that is inconsistent with their religious teachings. For example, unethical content, violence and social media often promote materialistic and hedonistic lifestyles, which are contrary to religious spiritual values. This research method uses a literature review type of research with a qualitative approach. The aim of the research is to understand how media social influences the learning process and practice of religious values ​​among children. This research aims to explore the extent to which social media can be an effective means of disseminating educational and inspirational religious content